Excitation of the Auditory System as a Result of Non-invasive Extra-Cochlear Stimulation in Normal Subjects and Tinnitus Patients - Mielczarek, Marzena; Norena, Arnaud; Schlee, Winfried; Olszewski, Jurek (Frontiers in Neuroscience, 2018)
One of possible approach that may suppress tinnitus is electrical stimulation of the ear. At first invasive techniques were used (promontory or round window stimulation), nowadays a non-invasive method, namely hydrotransmissive electric stimulation (ES) through external acoustic canal, has been developed. The aim of the study is to investigate the effect of applying ES with positive and negative current polarities on the ears of healthy subjects and on the tinnitus ears of patients with tinnitus. This comparison further clarifies the mechanisms of operation of non-invasive extra-cochlear ear ES. A second aim is to assess the effects of ES on tinnitus in tinnitus patients. The material was composed of two groups: tinnitus group—49 patients suffering from tinnitus, and healthy students group—34 healthy individuals. ES was performed with the use of a custom-made apparatus. The active, silver probe–was immersed inside saline filling external ear canal. The passive electrode was placed on the forehead. Positive and next negative DC stimulation was provided with the use following frequencies: 0.25, 1, 2, 3, 4, 5, 6, 7, 8 kHz. We checked for the presence of the auditory percept (AP) and, if AP was present, the minimum current amplitude necessary to produce AP was measured. In our research both positive and negative polarities were efficient to evoke AP in the participants. This effect, however, was more pronounced for positive polarity in no tinnitus and normal hearing individuals (healthy students group). In the tinnitus group, current intensity needed to evoke AP was higher than in the healthy students group. However, comparing normal hearing vs. hearing loss patients within the tinnitus group, we did not observe the relationship between hearing threshold and current intensity evoking AP. Afterwards, we analyzed the effect of multi-frequency ES on tinnitus. It appeared to be effective in 75% of tinnitus ears (with a high score of disappearance–22%). Our study proved that extracochlear ES with positive and negative current was efficient to stimulate the auditory system. Stimulating tinnitus ears with two polarities we obtained a higher ratio of improvement (75%) comparing to positive stimulations.